Development and Quality Assessment of Fiber Enriched Nuggets of Kadaknath Chicken - Uikey, Shubham; Nayak, Narendra (Journal of Meat Science, 2019)
The present investigation was carried out with the prime objective of increasing fiber content by incorporating gram hulls. Upon con ducting various trials, on the basis of sensory attributes three best levels were selected. Efficacy of gram hulls at three different selected levels (T1-4%, T2-6% & T3-8%) was assessed to increase the fiber content in kadaknath chicken nuggets. The pH value for control was significantly (P<0.05) higher as compared to treatment. Moisture content decreased gradually and showed a significant (P<0.05) differ ence at 6 % and 8 % incorporation of gram hulls. The fiber content in kadaknath chicken nuggets was increased significantly (P<0.05) with the increasing level of gram hulls. Moisture retention of gram hulls incorporated kadaknath chicken nuggets also differ significantly (P<0.05). Hardness value was increased gradually with the increasing level of gram hulls and become significant (P<0.05) at T-3. There was a significant (P<0.05) difference between control and T-3 in the adhesive force as well as cohesiveness value of high fiber kadak nath chicken nuggets. A non–significant (P>0.05) lower gumminess value was recorded for the product prepared with 4 % gram hulls as compared to control. The mean score value for overall acceptability showed that the score for T-3 was significantly (P<0.05) lower compared to control. However, score for T-2 was comparable to control. Hence, T-2 (6% gram hulls) was finally selected as optimum for incorporation to develop fiber enriched kadaknath chicken nuggets.